2020
DOI: 10.1128/jvi.01016-20
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mucosal Adjuvant System for Immunization against Avian Coronavirus Causing Infectious Bronchitis

Abstract: Infectious Bronchitis (IB) caused by Infectious Bronchitis Virus (IBV) is currently a major threat to chicken health with multiple outbreaks being reported in the US over the past decade. Modified live virus (MLV) vaccines used in the field can persist and provide the genetic material needed for recombination and emergence of novel IBV serotypes. Inactivated and subunit vaccines overcome some of the limitations of MLV with no risk of virulence reversion and emergence of new virulent serotypes. However, these v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 56 publications
4
35
0
Order By: Relevance
“…Th2 (IL-13+) and Tc2 responses were significantly lower in the heterologous vaccine group in the lungs and spleen of vaccinated mice ( Figures 5 and 6, respectively). Significantly higher S-specific Tc1 responses (predominantly IFN-γ+) were also present in the lungs of pQAC-CoV (I.N)-immunized mice without significant induction of CD4+ T-cells ( Supplementary Figure S3), an observation noted previously with QAC-DNA vaccination in chickens [11]. In addition, intramuscular (I.M) administration of pQAC-CoV alone induced significantly higher Th1 and Th17 responses in the spleen of vaccinated mice ( Figure 6).…”
Section: Sars-cov-2-specific Cellular Responses In Vaccinated Micesupporting
confidence: 76%
See 4 more Smart Citations
“…Th2 (IL-13+) and Tc2 responses were significantly lower in the heterologous vaccine group in the lungs and spleen of vaccinated mice ( Figures 5 and 6, respectively). Significantly higher S-specific Tc1 responses (predominantly IFN-γ+) were also present in the lungs of pQAC-CoV (I.N)-immunized mice without significant induction of CD4+ T-cells ( Supplementary Figure S3), an observation noted previously with QAC-DNA vaccination in chickens [11]. In addition, intramuscular (I.M) administration of pQAC-CoV alone induced significantly higher Th1 and Th17 responses in the spleen of vaccinated mice ( Figure 6).…”
Section: Sars-cov-2-specific Cellular Responses In Vaccinated Micesupporting
confidence: 76%
“…Earlier studies have shown that heterologous DNA/virus immunization is more immunogenic and protective than homologous virus/virus immunization strategies [38]. Based upon our previous experience with the avian coronavirus [11] and other studies with SARS-CoV [39,40], we selected both nucleocapsid (N) and spike (S) proteins as our antigen targets. Although we immunized mice concurrently with both the N and S vaccine constructs, we focused on characterizing the more biologically relevant humoral responses against spike, which neutralized and limited viral entry [41,42].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations